Prevalence and risk factors for low back pain among professional cooks working in school lunch services - Temmyo Yoshiomi; Tomita Shigeru; Ito Akiyoshi; Sakai Kazuhiro; Nagasu Miwako; Ueno Mitsuo; Miyagi Shigeji (BMC, 2007)
Abstract Background The prevalence of self-reported low back pain among professional cooks was estimated to examine the effects of daily life conditions, job-related factors, and psychological factors on this disorder. Methods Data was collected using a mailed self-administered questionnaire. Results Of 7100 cooks, 5835 (82%) replied to the questionnaire, including 1010 men and 4825 women. The mean age was 41.4 for men and 47.5 for women. The prevalence of low back pain during a 1-month period was 72.2% among men and 74.7% among women, with no significant differences between groups. By logistic regression analyses, factors significantly associated with the prevalence of low back pain in 1 month were female gender (prevalence ratio [PR] 1.32; 95% CI, 1.03-1.68), current smoking (PR 1.57; 95% CI, 1.24-1.98), and past smoking (PR 1.35; 95% CI, 1.01-1.79). As for job-related factors, the number of cooked lunches per person (PR 1.28; 95% CI, 1.05-1.56), breaks in the morning session (PR 1.33; 95% CI, 1.13-1.56), kitchen environment (PR 1.09; 95%, CI, 1.03-1.15), and height of cooking equipment (PR 1.13; 95% CI, 1.08-1.19) were associated with the prevalence of low back pain. As for psychological factors, job satisfaction (PR 1.22; 95% CI, 1.03-1.45), stress at work (PR 1.68; 95% CI, 1.42-1.99), financial constraints (PR 1.23; 95% CI, 1.03-1.47), health-related stress (PR 1.31; 95% CI, 1.08-1.59) and worries about the future (PR 1.24; 95% CI, 1.01-1.52) were similarly associated. Conclusion Daily life conditions, job-related factors, and psychological factors are associated with the occurrence of low back pain. It is important to take comprehensive preventive measures to address a range of work and life conditions that can be improved to decrease the incidence of low back pain for professional cooks.